Feasibility study of the propulsion force generated from the induced vibratory response of structures - Pereira, Gabriel Figueiredo (Seven Editora, 2023)
This work brings a brief physical and computational analysis on a mechanical system patent, whose authors claim to be able to generate movement from the vibration of its structure. This type of invention fits into a larger category of systems called reactionless engines, which have been shown to be unfeasible due to the violation of fundamental laws of motion. In order to demonstrate this, this study aims to bring a physical formulation of the proposed system’s mechanism and the inspection of its structure’s behavior when subjected to vibration at natural frequencies using finite elements modal analysis (FEA). Additionally, the discrepancies observed in the results for different models are pointed out. Through this methodology, the results obtained are complementary to each other, and, qualitatively, it was possible to conclude that the proposed system is not capable of producing propulsion once it disregards the conservation of momentum principle, like the others in the category. DOI: https://doi.org/10.56238/methofocusinterv1-078